The relationship between irritability, depression and anxiety among Chinese college students during the COVID-19 pandemic: A network analysis - Li, Ling; Ren, Lei; Zhan, Xiaoqing; Wang, Lingzhi; Liu, Chang; Zhao, Mengxue; Luo, Xi; Feng, Zhengzhi; Li, Kuiliang (Frontiers in Child and Adolescent Psychiatry, 2023)
Irritability, a common symptom included in the 5th Edition of Diagnostic and Statistical Manual of Mental Disorders (DSM-5), is thought to be associated with multiple emotional disorders. It is commonly seen among college students in isolation during the COVID-19 pandemic. However, its relation with anxiety and depression remains unclear. We aim to study the relation of irritability, anxiety and depression in Chinese college students during the COVID-19 pandemic by using network analysis to understand the co-occurrence of these three disorders. During the COVID-19 pandemic, we recruited 1516 college students from five general universities in China to complete the Irritability, Depression and Anxiety Scale (IDA-S) to analyze the symptom network of irritability, depression and anxiety. Specifically, we assessed the indices of strength centrality and bridge strength for each node in the network. Some strongest linkages were found among anxiety symptoms "nervous" and "panic" (weight=0.36), depression symptoms "sad mood" and "amused" (weight = 0.32), inward irritability items "self-hurt" and "self-harm" (weight = 0.32) and outward items "rough" and "aggressive" (weight = 0.28). The anxiety symptom "panic" had the highest strength value, followed by the inward irritability symptom "annoyed". The nodes "ease" and "sleep" had the lowest strength value. In addition, the anxiety symptom "relax" had the highest bridge strength value, followed by inward irritability symptom "annoyed". This study explored the characteristics of a network of irritability, depression and anxiety symptoms among Chinese college students during the COVID-19 pandemic. We found that anxiety and irritability symptoms played an important role in the network. The findings provide evidence for prevention and interventions for college students' mental health during the COVID-19.